Faktor yang mempengaruhi perubahan gaya hidup selepas tatacara koronari angioplasti - Yusof, Norizam Muhammad (2013)
Coronary Angioplasty Procedure (PTCA) is one of the treatments for coronary heart disease. PTCA is carried out to widen narrowed section of coronary arteries in a short time without requiring operation. However, renarrowing blood vessel after undergoing PTCA procedure is still being main problem. Lifestyle changes should be done continuously to reduce the risk of renarrowing the blood vessels. This study was carried out to identify lifestyle changes of the patients before and three months after undergoing PTCA procedure in Hospital Universiti Sains Malaysia (HUSM). A total of 75 patients participated in this study. This study was conducted through interviews by using Health Promoting Lifestyle Profile II (HPLP II) questionnaires. Descriptive and analytical analysis performed for demographic data and Paired t-test were used to compare the lifestyle changes of the patients before and three months after undergoing PTCA procedure. Multiple Regression analysis was used to identify demographic factors which influenced their lifestyle changes. Results showed that the overall lifestyles mean before PTCA procedure was 118.03 and 119.85 after PTCA procedure. The differences in mean score is -1.83 (t = -1.33, p = 0.19), showing that there was no significant difference of lifestyle before and after the PTCA procedure. There were no significant difference of mean score identified on four lifestyle subscales: health responsibility (t = 0:13, p = 0.89), physical activity (t = -0.18, p = 0.86), nutrition (t = -0.17, p = 0.86) and spiritual development (t = -0.84, p - 0:41). Only two lifestyle subscales showed significant differences in mean scores where for interpersonal relationship (t = -2.69, p = 0.01) and stress management (t = 0.001). The -5.44, p study found that gender, level of education, age and occupation influenced the lifestyle changes among patients after three months of PTCA procedures. This study clearly shows that the patients involved did not completely change the risky behaviors practiced before the procedure and they were at risk for experiencing a renarrowing of blood vessels which can cause heart attack and death. To overcome this problem a special instrument need to be structured so that patient’s lifestyle after undergoing PTCA procedure must always be assessed and prompt action can be taken.